The Determinants of Startup Business Growth in Indonesia: A Bibliometrical Analysis - Lantana, Dhieka Avrilia; Digdowiseiso , Kumba (CV ODIS, 2023)
Startups are companies that have had a major influence on the Indonesian economy especially in the past COVID-19 when with the presence of startups the circulation of money in the country is still awake. However, in its growth, the start-up company is currently experiencing constraints that have to dismiss many of its employees. Given how important startups are for the Indonesian economy, it is important to look for any determinants that could potentially influence the growth of startups in Indonesia. The researchers used quantitative methods using bibliometric analysis. The data used in the study were journals collected using Harzing’s Publish or Perish which were then curated by the researchers and analyzed using the VOSviewer application. The researchers found that out of the 29 journals obtained, only 20 corresponded to the study. The journal used was from 2018-2023 to keep the information on the study up to date. Based on the results of the analysis, the researchers found that the most powerful determinants to influence the growth of startup business in Indonesia are employee, Indonesia, startup growth, technology and the economy